PENERAPAN MODEL PEMBELAJARAN INTERAKSI PROMOTIF (FACE TO FACE PROMOTIVE INTERACTION) PADA MATERI HEWAN DAN TUMBUHAN DI LINGKUNGAN RUMAHKU UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 11 PIDIE - Abdul Manaf (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
This study aims to determine the application of the promotive interaction learning model (Face To Face Promotive Interaction) can improve the learning outcomes of fourth grade students of MIN 11 Pidie. The research method used is CAR. The population of this study was fourth grade students in the even semester of the 2020/2021 academic year. Data was collected using lesson plans, LOAS, LOAG, and LKS in 3 cycles in the first cycle the average value obtained was 66 and the percentage was 40%. In the second cycle the average value obtained by students was 71 and the percentage was 77%. In cycle III the average value obtained by students is 82 and the percentage is 100%.